Brand Snapshot: A new marketing tool - Dutta, Akanksha; Sharma, Dr. Anupam (The journal of contemporary issues in business and government, 2021)
It has been proposed that make and legacy usually summarizes a role in snapshot where the impression of brand and product arouses customers sentiments that take out the larger participation and accord to the in between activity with the brand. The purpose of this study is to understand how the snapshot experience could initiate the in between activities of the brands and the intended audience, in such a way that it can be used as a commercial instrument for the companies. A netnographic research tool has been used for the present study as it is the perfect combination of internet and ethnography which is designed to study the virtual communities. The involvement of brand snapshot postings on Zivame were considered by observing the users snapshot to forecast the brand utilization. A thoughtful sample of Zivame users was chosen, and from those, a total of 50 brand snapshots were observed.